Development of Learning Media Based on Using The Predict-Observe-Explain Model to Enhance Students' Mathematical Understanding Skills - Nenden Suryati; Irena Puji Luritawaty; Tina Sri Sumartini (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2026)
Learning in the subject of Three Variable Linear Equation Systems (SPLTV) still tends to focus on solution procedures, so that students' conceptual understanding has not developed optimally. This study developed a Google Sites-based learning medium integrated with the Predict-Observe-Explain (POE) model and examined its validity, practicality, and indications of effectiveness. The research used a Research and Development approach with ADDIE stages involving 40 tenth-grade high school students. Data were obtained through mathematical comprehension tests, expert validation sheets, and student response questionnaires, and analyzed descriptively using achievement percentages and N-Gain calculations. The validation results showed that the media was in the high validity category with a material expert assessment percentage of 90.3% and a media expert percentage of 84.7%, while student responses were in the practical category with a percentage of 75.23%. The improvement in mathematical comprehension ability was indicated by an average N-Gain score of 0.55, which is in the moderate category. These findings show that web-based media combined with the POE stages helped students compare their initial assumptions with their observations and systematically construct explanations of concepts, thereby supporting the formation of more meaningful mathematical comprehension.